Industrial application of atom probe tomography to semiconductor devices. (15th April 2018) - Giddings, Alexander Devin; Koelling, Sebastian; Shimizu, Yasuo; Estivill, Robert; Inoue, Koji; Vandervorst, Wilfried; Yeoh, Wai Kong
Abstract: Advanced semiconductor devices offer a metrology challenge due to their small feature size, diverse composition and intricate structure. Atom probe tomography (APT) is an emerging technique that provides 3D compositional analysis at the atomic-scale; as such, it seems uniquely suited to meet these challenges. However, the semiconductor industry has demanding requirements against which the techniques in use are evaluated. This article explores the use of APT in the semiconductor industry, showing the potential of the technique, the obstacles that occur in practise, and possible future developments. Graphical abstract: Image 1